Incidence and risk factors for falls among community-dwelling elderly subjects on a 1-year follow-up: a prospective cohort study from Ernakulam, Kerala, India - Manu Raj; Abish Sudhakar; Conrad Kabali; Divyamol K Sasidharan; Priya Vijayakumar; Sumi Soman; Libin Antony (BMJ Open)
Objectives There is limited knowledge regarding epidemiology and risk of falls among the elderly living in low-income and middle-income countries. In this situation, the current study aims to report the incidence of falls and associated risk factors among free living elderly population from Kerala, India.Design Prospective cohort study with stratified random cluster sampling.Setting The study location was Ernakulam, Kerala, India, and we collected information via house visits using a questionnaire. During the research, the subjects were followed up prospectively for 1 year by phone at intervals of 3 months and missing subjects were contacted by house visits.Participants Community-dwelling elderly above 65 years of age.Results We recruited a total of 1000 participants out of which a total of 201 (20.1%) subjects reported a fall during the follow-up. The incidence rate of falls was 31 (95% CI 27.7 to 34.6) per 100 person-years. Female sex (OR 1.48, 95% CI 1.05 to 2.10, p=0.027), movement disorders including Parkinsonism (OR 2.26, 95% CI 1.00 to 5.05, p=0.048), arthritis (OR 1.48, 95% CI 1.05 to 2.09, p=0.026), dependence in basic activities of daily living (OR, 3.49, 95% CI 2.00 to 6.09, p<0.001), not using antihypertensive medications (OR, 1.53, 95% CI 1.10 to 2.13, p=0.012), living alone during daytime (OR 3.27, 95% CI 1.59 to 6.71, p=0.001) and a history of falls in the previous year (OR, 2.25, 95% CI 1.60 to 3.15, p<0.001) predicted a fall in the following year.Conclusions One in five community-dwelling senior citizen fall annually and one in four who fall are prone to fall again in the following year. Interventions targeting falls among the elderly need to focus on modifiable risk factors such as living alone during daytime, movement disorders, arthritis and dependence on basic activities of daily living.